Assessment of evapotranspiration of licorice under saline environments: case study from Galaba farm, Uzbekistan (ҚазҰУ хабаршысы. Экология сериясы, 2022)
Land salinization is widespread in countries of the arid zone, including in the Aral Sea basin, where 4 million hectares of irrigated land are salt-affected, causing high economic losses. Current saline soil reclamation practices include soil leaching and deep drainage to remove excess water outside the irrigated zone. Growing pressure on limited water resources makes this practice ineffective. An alternative is biological methods of salinity control, which are not widely used in the region. In this study, the licorice plant was considered a potential crop for restoring the fertility of salt-affected soils. The study has two objectives: (1) to assess evapotranspiration from licorice fields, and; (2) to track changes in soil chemical properties as affected by the cultivation of licorice on irrigated land. The results of the study indicate high evapotranspiration from licorice fields under irrigation. The total amount of soluble salts may increase in the soil profile; however, after more than 10 years of cultivation of the crop, no accumulation of toxic salts has occurred and there was no deterioration in the chemical and water-physical properties of soils, while at the same time soil fertility has increased.Key words: Soil salinization, Aral Sea basin, licorice, biological reclamation, soil fertility.